Meningkatkan Kemampuan Memahami Konsep Ruang bagi Anak Gangguan Spektrum Autisme Menggunakan Media Sensory Path Space (Single Subject Research Kelas II di SLB Al-Ikhlas Bukittinggi) - Sari, Salmaa Kurnia; Taufan, Johandri; Rahmahtrisilvia, Rahmahtrisilvia; Budi, Setia (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by problems found in students with mild autism spectrum disorder in class II at SLB Al-Ikhlas Bukittinggi who do not have the ability to understand the concepts of right and left directions. This study aims to improve the ability to understand spatial concepts using Sensory Path Space media. The research method used is a quantitative experimental method, specifically a Single Subject Research (SSR) design A-B. The subject of this study is a child with mild autism spectrum disorder at SLB Al-Ikhlas Bukittinggi. Data were collected through action tests with visual graph data analysis, which served as the analysis within and between conditions. The research results indicate that the use of Sensory Path Space media can improve the ability to understand spatial concepts in children with autism spectrum disorder, as evidenced by an increase in scores from a stable baseline phase of 33.33% to 83.33% during the intervention phase. Nevertheless, this study has limitations because it involved only one subject, focusing on the concepts of right and left space, and the child's responses were not always consistent throughout the intervention process. Therefore, it is recommended that future research involves more subjects, expands the coverage of spatial concept material, and develops more innovative and adaptive learning media so that the research results can be more optimal and have broader generalizability.